Hedgehog Signaling in Organogenesis and Tumor Microenvironment - Shimo, Tsuyoshi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Hedgehog signaling pathway is an evolutionarily conserved pathway that governs complex developmental processes, including stem cell maintenance, proliferation, differentiation, and patterning. Several recent studies have shown that the aberrant activation of Hedgehog signaling is associated with neoplastic transformation, cancer cell proliferation, metastasis, multiple cancers' drug resistance, and survival rates. This book focuses on several aspects of Hedgehog signaling in organogenesis and the tumor microenvironment, and presents reviews and original papers on recent efforts in the field of Hedgehog signaling.